English Language Education Students' Perception on the Use of AI in English Language Teaching - Liunokas, Yanpitherszon (Institut Agama Islam Negeri Palopo, 2025)
This study investigates English Language Education students' perceptions regarding the integration and utilization of Artificial Intelligence (AI) technologies in English Language Teaching (ELT). The research aims to explore students' attitudes toward AI-assisted language learning tools, examine their perceived benefits and challenges of AI implementation in ELT contexts, and identify factors that influence their acceptance of AI technologies in language education. A qualitative descriptive methods approach was employed, the study involved 150 English Language Education students, Nusa Cendana University. Data were collected through a structured questionnaire measuring perceptions, attitudes, and experiences with AI in language learning. and thematic analysis for qualitative data were conducted to examine the research questions. The findings reveal that English Language Education students generally hold positive perceptions toward AI integration in ELT, particularly regarding AI's potential to enhance personalized learning experiences and provide immediate feedback. Students recognized AI tools' effectiveness in improving pronunciation, grammar checking, and vocabulary acquisition. However, concerns emerged regarding AI's limitations in understanding cultural nuances, potential over-dependence on technology, and the irreplaceable value of human interaction in language learning. Keyword: Artificial Intelligence AI, English Language Teaching (ELT), Student Perception